1989
DOI: 10.1007/bf00043202
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the kafirin gene family from sorghum reveals extensive homology with zein from maize

Abstract: Electrophoretic analysis of translation products of polyadenylated RNA isolated from mid-maturation sorghum seed in the presence of [(35)S]met, [(3)H]leu, or [(3)H]val revealed two major proteins of kDa and 21 kDa. These products were not detected when [(3)H]lys was supplied as the radioactive substrate. Under similar electrophoretic conditions, kafirin (a major seed storage prolamin of sorghum), migrated as two bands of 22 kDa and 19 kDa. Sequence analysis of two cDNA clones (pSK8 and pSKR2) from sorghum seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 44 publications
4
63
0
Order By: Relevance
“…Macroscopic and histological evaluation showed no abnormal pathology for any of the organs from rats implanted with any of the treatments at both time intervals. Overall, the data showed that kafirin microparticle film implants, including films treated with glutaraldhyde, sorghum polyphenols or rhBMP-2 were non-irritant to the rats, agreeing with studies showing that zein, which is homologous to kafirin, 11 has good cell compatibilitl· 30 and has shown no adverse effects when used as a scaffold material in animal studies.…”
Section: Implant Biocompatibility Assessment Rat Modelsupporting
confidence: 79%
See 1 more Smart Citation
“…Macroscopic and histological evaluation showed no abnormal pathology for any of the organs from rats implanted with any of the treatments at both time intervals. Overall, the data showed that kafirin microparticle film implants, including films treated with glutaraldhyde, sorghum polyphenols or rhBMP-2 were non-irritant to the rats, agreeing with studies showing that zein, which is homologous to kafirin, 11 has good cell compatibilitl· 30 and has shown no adverse effects when used as a scaffold material in animal studies.…”
Section: Implant Biocompatibility Assessment Rat Modelsupporting
confidence: 79%
“…6 Zein has been shown to have good bio-and cyto-compatibility. 7 In vivo studies of zein scaffolds have shown good tissue response and biodegradability 8 • 9 Further, complexes of zein scaffolds and rabbit mesenchymal stem cells have been shown to undergo ectopic bone formation in the thigh muscle pouches of nude mice, 10 Kafirin is the homologous sorghum protein to zein, 11 and may have some advantages over zein for use in biomedical applications. Kafirin is usually considered more hydrophobic/ 2 is less digestible, 12 and has a higher glass transition temperature than zein.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, 22 members are tandemly arrayed within 168 kb, whereas one copy is located 20 cM closer to the centromere of maize Chromosome 4S. Sorghum also has a storage protein, 22-kD kafirin, homologous to the maize 22-kD zein (DeRose et al 1989). Rice does not have a corresponding storage protein (Kim and Okita 1988).…”
mentioning
confidence: 99%
“…Schmidt et al (1992) suggested that O2 may interact with factors binding the P-box to activate 22-kDa zein gene expression. It was reported that 7 bp P-box sequence was common in cereals like oats (Shotwell et al 1990), wheat (Colot et al 1987), barley (Marris et al 1988), and sorghum (DeRose et al 1989) and plays a key role in regulating the endospermspecific expression.…”
Section: Discussionmentioning
confidence: 99%